Plant diversity and transcriptional variability assessed by retrotransposon-based molecular markers - R. N. Kalendar; K. S. Aizharkyn; O. N. Khapilina; A. A. Amenov; D. S. Tagimanova (Вавиловский журнал генетики и селекции, 2017)
Molecular markers have become crucial part of genetics due to their use in various branches of it, such as positional cloning, which includes identification of genes responsible for desired traits and management of backcrossing programs, as well as in modern plant breeding, and human forensics. Retrotransposons are a major component of all eukaryotic genomes, which makes them suited as molecular markers. The retrotransposons comprise most of large genomes among plants; differences in their prevalence explain most of the variation in genome size. These ubiquitous transposable elements are scattered in all of genome and their replicative transposition allows insert itself into a genome without deletion of the original elements. Retrotransposon activity can occur during development, cell differentiation and stress, and a source of chromatin instability and genomic rearrangements. Both the overall structure of retrotransposons and the domains responsible for the various phases of their replication are highly conserved in all eukaryotes. A high proportion of the retroelements have lost their autonomous transposition ability, either by point mutations and/or deletions, many of them seem to embody defective elements with deletions. Various molecular marker systems have been developed that exploit the ubiquitous nature of these genetic elements and their property of stable integration into dispersed chromosomal loci that are polymorphic within species. The utility of LTR-retrotransposon-based markers, not only for genetic analysis and map construction, in addition also for the isolation and characterization of LTR retrotransposons, such as the long terminal repeats or the internal genes they contain. This review encompasses description of the range of retrotransposon-based marker systems established for plants and evaluation of the role of retrotransposon markers in genetic diversity analysis of plant species.